Electomsgnetism for Engineers - Hammond, P. (Oxford : University Press, 1997)
Engineering
Keywords: Electromagnetism; Engineers; Electrical; Electronic; Engineering; Electric Charges; Electromagnetic Fields; Electromagnetic Induction; Electric Currents; Magnetic Effects; Electromechanics; Electromagnetic Rediation; Electromagnetic Interference; Electricity; Electromagnetic Interactions